2021
DOI: 10.3389/fneur.2021.673135
|View full text |Cite
|
Sign up to set email alerts
|

Results From an Italian Expanded Access Program on Cannabidiol Treatment in Highly Refractory Dravet Syndrome and Lennox–Gastaut Syndrome

Abstract: Background: Purified cannabidiol (CBD) was administered to highly refractory patients with Dravet (DS) or Lennox–Gastaut (LGS) syndromes in an ongoing expanded access program (EAP). Herein, we report interim results on CBD safety and seizure outcomes in patients treated for a 12-month period.Material and Methods: Thirty centers were enrolled from December 2018 to December 2019 within the open-label prospective EAP up to a maximum of 25 mg/kg per day. Adverse effects and liver function tests were assessed after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 21 publications
2
27
0
1
Order By: Relevance
“…Increases in transaminases at similar dose levels were also found in open‐label extensions of these trials as well as other open‐label studies with patients with epilepsy with durations of up to 2 years (Devinsky et al., 2016 , 2019 ; Szaflarski et al., 2018 ; Sands et al., 2019 ; Thiele et al., 2019 ; D’Onofrio et al., 2020 ; Iannone et al., 2021 ).…”
Section: Limitations and Uncertainties In Scientific Literaturesupporting
confidence: 70%
See 1 more Smart Citation
“…Increases in transaminases at similar dose levels were also found in open‐label extensions of these trials as well as other open‐label studies with patients with epilepsy with durations of up to 2 years (Devinsky et al., 2016 , 2019 ; Szaflarski et al., 2018 ; Sands et al., 2019 ; Thiele et al., 2019 ; D’Onofrio et al., 2020 ; Iannone et al., 2021 ).…”
Section: Limitations and Uncertainties In Scientific Literaturesupporting
confidence: 70%
“…Several open‐label trials also reported the occurrence of diarrhoea as the most common and consistently observed gastrointestinal effect associated with oral intake of CBD, albeit none of them included placebo or control groups. Most of these studies were again on patients suffering from epilepsy of various aetiologies (age range 0.4–62 years), whereby purified plant‐derived CBD or, in one case, also synthetic (+)CBD was given as adjunctive therapy to multiple antiepileptic medication (Devinsky et al., 2016 , 2019 ; Klotz et al., 2019 ; Laux et al., 2019 ; Sands et al., 2019 ; D'Onofrio et al., 2020 ; Gaston et al., 2021 ; Iannone et al., 2021 ; Patel et al., 2021 ). These studies included between 26 and 607 patients, who ingested doses of 14 up to 32 mg/kg bw per day over periods varying between 12 weeks up to 2 years.…”
Section: Limitations and Uncertainties In Scientific Literaturementioning
confidence: 99%
“…Cannabidiol was also associated with improvements in overall condition assessed using the Caregiver Global Impression of Change, as well as increases in seizure-free days. Longer term efficacy and safety (up to 3 years) has been determined in an open-label extension of the pivotal phase III trials [ 67 , 68 ], and importantly from an expanded access programme confirming its efficacy in real-world clinical practice [ 69 72 ].…”
Section: Highly Purified Cannabidiol (Cbd)mentioning
confidence: 99%
“…Nowadays, CBD's efficacy was demonstrated in five placebo-controlled pivotal trials, two conducted in LGS (190,191), two in DS (53,192), and one in epilepsy associated with TSC (13). Furthermore, numerous expanded access use studies as well as open label extension of RTCs have been published so far (193)(194)(195)(196)(197)(198) and numerous comprehensive reviews and metanalysis investigating the clinical…”
Section: Epilepsymentioning
confidence: 99%